Estado fitosanitario de Cedrelinga cateniformis (Ducke) de diferentes edades mediante técnicas acústicas no destructivas Loreto-Perú 2023 - Garay Vásquez, Kattia (2024)
This work shows the phytosanitary status of Cedrelinga cateniformis (Ducke) Ducke plantations of different ages at the Puerto Almendra Forestry Research and Teaching Center in Loreto, Peru, using a non-destructive technique such as Arbosonic 3D acoustic tomography in plantations of different ages, established in soils with nutritional deficiencies, sandy loam texture, and extremely acidic pH. The results allowed us to identify the degree of deterioration of the trees despite not having external defects. It was found that at 16 years of age the plantation's health affectation is 6%, while from 25 years of age the affectation can reach up to 42%; there is a moderate positive linear correlation between the age of the plantation and the affectation at a probability of 95%, that is, the older the age, the more affectation, presumably due to medullary rot.